Effect of in-season generic and soccer-specific high-intensity interval training in young soccer players - Jastrzebski, Z.; Barnat, W.; Dargiewicz, R.; Jaskulska, E.; Szwarc, A.; Radziminski, L. (International Journal of Sports Science and Coaching, 2014)
The main purpose of this study was to determine the effect of different interval training regimes on the physical capacity and soccer-specific skills of young soccer players. Twenty-two subjects were divided into two groups: small-sided games group (SSGG; age: 15.8 ± 0.63 y, body mass: 61.6 ± 8.97 kg, height: 175.0 ± 6.23 cm) or interval-running group (IRG; age: 15.8 ± 0.55 y, body mass: 62.7 ± 8.69 kg, height: 177.6 ± 6.48 cm). The groups completed two different 8-week training programs. The intervention consisted of two training sessions per week (IRG - 7 x 3 min running where each bout consisted of 15 s of high-intensity running and 15 s of jogging with an active recovery period of 3 min; SSGG - 3 vs. 3 games for 7 x 3 min, with an active recovery period of 3 min). Significant changes over time were found in VO2max (p = 0.009, 2 = 0.29) and peak power (p = 0.014, 2 = 0.26). Post-hoc analysis revealed a significant increase in the maximal oxygen uptake only in the SSG group (p = 0.019). No significant improvement in running speed was found. The mean HR at AT increased significantly in both groups. A relevant correlation (group x time) was found for oxygen uptake at the AT intensity (p = 0.015, 2 = 0.26). A significant time effect was also present with respect to this variable (p = 0.000, 2 = 0.61). Post-hoc analysis of the VO2/AT index revealed no relevant (p = 0.19) improvements in the IRG (from 44.1 ± 5.72 to 46.0 ± 5.03 ml·kg-1·min-1), but there was a significant (p = 0.000) increase in the SSG (from 40.9 ± 3.51 to 46.0 ± 3.88 ml·kg-1·min-1). The improvement in soccer-specific skills was not significant (3.2 % in IRG and 5.3 % in SSGG). The results of this study show that small-sided games and running can both be efficient training strategies for developing aerobic capacity and soccer-specific skills.